The impact of discretionary measurement criteria on investors' judgement and decisions - Tiago Cruz Gonçalves (Games, 2022)
This study investigates the effect on nonprofessional investors' judgements and decisions of discretionary measurement choices. Using a paper-and-pencil experience, we collect and analyze information regarding investment amounts as well as past and future financial performance judgements of firms' earnings by manipulating fair value (mark-to-market and mark-to-model) criteria and benchmarking it with historical cost-based financial statements. We proxy nonprofessional investors with graduate students from a business school. Our results show evidence that nonprofessional investors view fair value changes as permanent. We argue for a cashflow volatility factor. Contrary to previous research, we do not find evidence of any effect on investors' willingness to invest (average budget amounts invested) or performance judgments (past and future). We corroborate previous evidence that investors rank measurement concepts' relevance differently for different classes, although, on average, mark-to-market fair values and historical cost are rated more relevant and reliable than mark-to-model fair values.
Keywords: 330; fair value; judgement and decision; mark-to-market vs. mark-to-model; measurement theory; nonprofessional investors